Peningkatan kepatuhan pelaku usaha home industry terhadap perizinan dengan sistem pendekatan pemerintahan dan masyarakat - Arini, Hesty Rinda (Maliki Interdisciplinary Journal, 2024)
The purpose of doing this paper is to find out how to discuss the role of the government and community support in escorting and assisting home industry business actors to have legal compliance related to business licensing which has been regulated by the government. the method used for data collection in this paper is the library research method. It can be concluded that having business legality or a business license is very important to legalize the identity of a business and make it officially recognized by the public. Business legality is the recognition given by the state to a business so that it can be used as a requirement for cooperation with various parties. Increasing the compliance of home industry businesses with licensing also comes from the government and the community to create a conducive and highly competitive business environment at the local level. The government and the community must work together in creating an effective approach system to increase business actors’ compliance with licensing. Information and communication technology (ICT) can be used to increase the effectiveness of supervision and law enforcement against business actors who do not comply with permits. In addition, ICT can also strengthen partnerships between the government and the community in increasing business actor compliance with licensing. Home industry business actor compliance with licensing has a major positive impact on local economic growth, such as increasing regional income, increasing investment, increasing business growth, increasing product quality, and encourage local industry growth.